Inflammation-related pathways involved in damaged articular cartilage of rats exposed to T-2 toxin based on RNA-sequencing analysis - Shi, Longyan; Liu, Qiuliang; Yang, Heying; Wang, Qi; Wang, Jiaxiang; Fan, Yingzhong (Frontiers in Genetics, 2022)
Many studies have shown ingestion of the T-2 toxin is harmful to articular cartilage. However, the mechanisms underlying damaged articular cartilage induced by T-2 toxin have not been elucidated. Twenty-four SD rats were randomly divided into T-2 toxin and control groups. In control group the 12 rats were administered 4% absolute ethanol by gavage, and in T-2 toxin group the 12 rats were administered T-2 toxin (100 ng/g, BW/day) by gavage. After the rats were sacrificed, the knee joints were collected, and RNA was extracted using TRIzol Reagent for RNA-sequencing (RNA-seq). Differentially expressed mRNA were identified based on P < 0.05 and | log2 (fold change) | > 1. The T-2 toxin-related genes were obtained from the GeneCards database. An online tool (https://www.bioinformatics.com.cn) was used for enrichment analysis. Hematoxylin and eosin (H&E) staining was used to observe damaged articular cartilage, and Immunohistochemical (IHC) staining was used to validate differentially expressed proteins. The H&E staining shown the number of cells decreased significantly, and the arrangement of chondrocytes became disordered in the T-2 toxin group. RNA-seq analysis identified 195 up-regulated and 89 down-regulated mRNAs in T-2 toxin group. The top immune-related biological processes (Gene Ontology) were regulation of hormone secretion, regulation of peptide hormone secretion, and regulation of transcription involved in cell fate commitment. KEGG pathway enrichment analysis revealed IL-17 and TNF signaling pathway were significantly expression, and the IL-17 signaling pathway was also identified in the enrichment analysis of T-2 toxin related genes. And Mmp3, Tnf, Mapk10, Ccl11, Creb5, Cxcl2, and Cebpb were significantly enriched in the two pathways. The IHC showed the levels of Mmp3 and Tnf proteins were significantly increased in the T-2 toxin group, which was consistent with the RNA-seq results. This study revealed the critical role of IL-17 and TNF signaling pathways in damaged cartilage induced by T-2 toxin.